VicHealth Coronavirus Victorian Wellbeing Impact Study (Victorian Government; VicHealth, 2020)
Results of the VicHealth Coronavirus Victorian Wellbeing Impact Study - a comprehensive survey of 2,000 Victorians in the first coronavirus lockdown of 2020. One part is physical activity. Other parts are social connection, healthy eating and positive impacts.